Development of Picture Storybooks Based on Scientific Approaches in Science Lessons Class V SDN 36 Mataram Academic Year 2023 - Baiq Nidya Rizki Karima (Syntax Corporation Indonesia, 2023)
Based on the observation results at SDN 36 Mataram, several weaknesses were identified within the learning process. These include an emphasis on completing lesson materials rather than fostering understanding and meaningfulness of the subjects for students. Many students still engage in play during lessons, and a significant number of them hesitate to express their opinions due to a lack of confidence. The purpose of this research is to ascertain the development procedure of picture storybooks based on a scientific approach for fifth-grade Science lessons. This study falls under the category of research and development. It was conducted at SDN 36 Mataram, specifically in the fifth-grade classrooms. The research took place during the first semester of the 2023 academic year. The population of this study comprised all fifth-grade students at SDN 36 Mataram, while the sample included six students randomly selected from the fifth-grade class. This research employed the 4D model (define, design, development, and dissemination), focusing exclusively on the development phase with a sample of six participants (limited trial). The decision to choose six students as participants was based on specific reasons. Data collection techniques used in this study encompassed observation, documentation, and questionnaires. Both qualitative and quantitative analysis techniques were applied. This study involves the development of picture storybooks based on a scientific approach for fifth-grade students. The development of the scientific-based picture storybook follows the 4D development design, involving the phases of defining, designing, developing, and disseminating.